Researches in the field of counter-trafficking (Academic Journal of Internal Affairs, 2022)
Aim: Several forward-thinking researches have taken place in the topic of trafficking in human beings over the past two years. The review essay presents the scope of the research projects, their key features and findings, thus encouraging professionals working in this field as well as the wider audience to take a closer look at them.Methodology: For the above purpose, three handbooks are presented below.Findings: The research activities help to define government measures to combat human trafficking with reliable, scientific results.Value: The researches revealed the gaps and possible improvements of the victim support system and also contributed to a deeper understanding of the phenomenon.
Keywords: trafficking in human beings; exploitation; research; victim assistance